Resource development in tribal India - Sharma , S .K (New Delhi, 1989)
It is a treatise of the consequential problems of interactions between popu lation, resources and development. Resources play such a vital role in our economy that the evaluation of territorial distribution of resource-complexes and their potentialities for a balanced and integrated development cannot be dis associated from the wider field of planning for regional development. But the degree of exploitation of development potentials depends heavily upon human, socio political and economic-technological factors; and variation in these attributes of man causes variation in resource evaluation and their utilization. In the present politico-economic structure those people who are conscious of their rights and those areas which are dominated by such people get benefits of develop mental efforts. The tribal people and areas dominated by them could not exert decisive influence on decision-making of resource utilisation and development planning. Consequently, all transportable resources are exported out of such regions. This vicious mechanism of keeping poor people and poor region still backward has been critically analysed in the present book, citing the example of the Baghelkhand plateau-a resource rich region in the eastern Madhya Pradesh. Based on extensive field-work and long observations, this study squarely presents a dissection of the geographic, economic and cultural factors of utter backwardness in this peripheral tribal region. Through the spatio-temporal analysis of resource development and utilisation during the planning period it suggests remedial measures in the existing pattem and perspectives of resource use in the light of the concept of resource management and aimed at vigorous economic upheaval of the region.
Keywords: India